Nationwide assessment of practice variability in the utilization of hysteropexy at laparoscopic apical suspension for uterine prolapseAJOG Global Reports at a Glance - Kaily R. Cox, MD; Tanaz R. Ferzandi, MD, MBA; Christina E. Dancz, MD, MPH; Rachel S. Mandelbaum, MD; Maximilian Klar, MD, MPH; Jason D. Wright, MD; Koji Matsuo, MD, PhD (Elsevier, 2024)
BACKGROUND: Although hysteropexy has been used to preserve the uterus during uterine prolapse surgery for a long time, there is a scarcity of data that describe the nationwide patterns of use of this surgical procedure. OBJECTIVE: This study aimed to examine the national-level use and characteristics of hysteropexy at the time of laparoscopic apical suspension surgery for uterine prolapse in the United States. STUDY DESIGN: This cross-sectional study used data from the Healthcare Cost and Utilization Project's Nationwide Ambulatory Surgery Sample. The study population included 55,608 patients with a diagnosis of uterine prolapse who underwent laparoscopic apical suspension surgery from 2016 to 2019. Patients who had a hysterectomy were assigned to the hysterectomy group, and those who did not have a hysterectomy were assigned to the hysteropexy group. The main outcome was clinical characteristics associated with hysteropexy, assessed using a multivariable binary logistic regression model. A classification tree was further constructed to assess the use pattern of hysteropexy during laparoscopic apical suspension procedures. The secondary outcome was surgical morbidity, including urinary tract injury, intestinal injury, vascular injury, and hemorrhage. RESULTS: A hysteropexy was performed in 6500 (11.7%) patients. In a multivariable analysis, characteristics associated with increased use of a hysteropexy included (1) patient factors, such as older age, Medicare coverage, private insurance, self-pay, and medical comorbidity; (2) pelvic floor dysfunction factor of complete uterine prolapse; and (3) hospital factors, including medium bed capacity center and location in the Southern United States (all P<.05). Conversely, (1) the patient factor of higher household income; (2) gynecologic factors such as uterine myoma, adenomyosis, and benign ovarian pathology; (3) pelvic floor dysfunction factor with stress urinary incontinence; and (4) hospital factors including Midwest and West United States regions and rural setting center were associated with decreased use of a hysteropexy (all P<.05). A classification tree identified a total of 14 use patterns for hysteropexies during laparoscopic apical suspension procedures. The strongest factor that dictated the use of a hysteropexy was the presence or absence of uterine myomas; the rate of hysteropexy use was decreased to 5.6% if myomas were present in comparison with 15% if there were no myomas (P<.001). Second layer factors were adenomyosis and hospital region. Patients who did not have uterine myomas or adenomyosis and who underwent surgery in the Southern United States had the highest rate of undergoing a hysteropexy (22.6%). Across the 14 use patterns, the percentage rate difference between the highest and lowest uptake patterns was 22.0%. Patients who underwent a hysteropexy were less likely to undergo anteroposterior colporrhaphy, posterior colporrhaphy, and sling procedures (all P<.05). Hysteropexy was associated with a decreased risk for measured surgical morbidity (3.0 vs 5.4 per 1000 procedures; adjusted odds ratio, 0.57; 95% confidence interval, 0.36-0.90). CONCLUSION: The results of these current, real-world practice data suggest that hysteropexies are being performed at the time of ambulatory laparoscopic apical suspension surgery for uterine prolapse. There is substantial variability in the application of hysteropexy based on patient, gynecologic, pelvic floor dysfunction, and hospital factors. Developing clinical practice guidelines to address this emerging surgical practice may be of use.